Novel antibiotics in development to treat Clostridium difficile infection. Issue 1 (January 2017) - Bassères, Eugénie; Endres, Bradley T.; Dotson, Kierra M.; Alam, M. Jahangir; Garey, Kevin W.
Abstract : Purpose of review: Clostridium difficile infections (CDI) remain a challenge to treat clinically due primarily to limited number of antibiotics available and unacceptably high recurrence rates. Because of this, there has been significant demand for creating innovative therapeutics, which has resulted in the development of several novel antibiotics. Recent findings: This review updates seven different antibiotics that are currently in development to treat CDI including fidaxomicin, surotomycin, ridinilazole, ramoplanin, cadazolid, LFF571, and CRS3123. Available preclinical and clinical data are compared between these antibiotics. Summary: Many of these new antibiotics display almost ideal properties for antibiotics directed against CDI. Despite these properties, not all clinical development of these compounds has been successful. These studies have provided key insights into the pathogenesis of CDI and will continue to inform future drug development. Successful phase III clinical trials should result in several new and novel antibiotics to treat CDI.